Reframing Deception: Redefining the Fraud Triangle in the Era of Ethical Governance - Yuliani Almalita; Rudi Setiadi Tjahjono (Owner : Riset dan Jurnal Akuntansi, 2026)
This study reviews the evolution of the Fraud Triangle Theory (FTT) from 2010 to 2025 and examines how digital transformation and sustainability issues reshape its explanatory relevance. Using the PRISMA 2020 protocol, a Systematic Literature Review was conducted on 26 Scopus-indexed articles. Descriptive, content, and bibliometric analyses were applied to identify publication trends, methodological patterns, and theoretical developments. Results show that 76% of studies used qualitative or mixed methods, while only 24% employed quantitative or data-driven approaches. Research output peaked in 2022 with 12 publications, and the United States, China, and Indonesia accounted for 54% of contributions. Although FTT remains the dominant framework, 31% of studies integrated Agency Theory, Signaling Theory, or Critical Discourse Analysis. Fraud research increasingly addresses digital governance, ESG violations, and greenwashing. These findings position FTT as a dynamic model shaped by ethical, technological, and institutional forces, underscoring the need for hybrid behavior data analytical frameworks.